The transcriptional programs of iNKT cells. Issue 1 (February 2015) - Kim, Edy Y.; Lynch, Lydia; Brennan, Patrick J.; Cohen, Nadia R.; Brenner, Michael B.
Highlights The iNKT cell transcriptome is distinct from other innate and adaptive lymphocytes. EGR2, PLZF and microRNA regulate the iNKT cell transcriptome during development. Specific transcription factors define functional subsets of mature iNKT cells. The transcription factor PLZF influences iNKT cell homing to specific tissues.